Cute style in clothing according to selected female adopters of cute fashion in the University of the Philippines Diliman - Paguyo, Aura Barbra F. (Quezon City College of Home Economics, University of the Philippines Diliman, 2005)
Cute fashion finds its origin in the 'kawaii' of Japan, which when translated, means 'cute'. 'Kawai' is a modern aesthetic, a style, a taste, affection: it signifies anything small, cute, vulnerable and childlike that stimulates a feeling of pitiful love. (Hauser, 2004) It is a modifier that means cool, bitchin', groovy, killer and I-love-it all rolled into one, then squared'. (Drake, 2001) 'Kawaii' is a persisting element that has shaped the fashion and culture of Japanese youth. It is a cauldron unto which 'more specific and transient fashions such as preppy, punk, skater, folk, black and French were mixed'. It is popularity has generated a unique lucrative youth market; brand labels recognize the persuasive power of trend setting girls who were unique, interesting clothes. These karisuma tenin (charismatic salesgirls) determine what is and what is not 'kawaii'. (Drake, 2001) "Kawaii's' influence has already penetrated western and neighboring Asian fashions and their teens as well. In the University of the Philippines Diliman, there were visual but undocumented evidences of cute fashion exhibited by young female students. These adopters of cute fashion have their own unique style which differentiates them from the rest. This research paper was developed to define cute style in clothing according to these self-professed adopters of cute fashion. The specific objectives of this study were to identify the trims and visual design elements: colors, prints and shapes (style features, collar styles, bodice/blouse/shirt styles, skirt styles, dress styles) considered cute by the adopters of cute fashion in the University of the Philippines Diliman and to describe cute fashion based on the selected respondents' definition and exhibition of cute style in clothing and description of a "cutie", approach to dressing cute clothing based on the framework of 'kawaii'. Respondents were selected through snowball sampling, which relied on the referrals from the initial respondents. There were 11 self-professed adopters of cute fashion who participated in this research. Data were obtained through combined survey questionnaire and interview. Descriptive statistical methods and content analysis were used to interpret the results. According to the results obtained, cute fashion, like the people who adopt it, is colorful and accessorized. It is Japan/ 'kawaii'-inspired and involves fun, spontaneous, playful, childlike, self-expressive, defiant, imaginative, experimental and creative approaches in creating cute ensembles. It is not boxed to a certain look and can be subjective. Trims and visual design elements which evoke the psychological effect of youthfulness and happiness were considered cute by the practitioners. Most of the details and style elements identified as cute were either uniquely detailed or childlike in appearance.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman.
Keywords: Clthing and dress -- Philippines; Fashion design -- Philippines